Critical Analysis of Interdisciplinary Healthcare Delivery Models, Communication, And Patient Outcomes - Al Rashah, Hamzah Saleh Abdullah; Asiri, Amal Abdullah Bin Saad; al rasha, Ibrhim Ahmed; Al ishaq, Rizq Mohammed Rizq; Alkhayawani, Ahmed Saleh Yahya; Alrashah, Abdulaziz Ahmad Mohsen; al rashah, Khaled ali; Alrashah, Saleh Mohammed; Al Rashah, Naief Abdullah Y; Al Rashah , Ali Ahmed Mohsen (Journal of Ecohumanism, 2024)
Integrating interdisciplinary healthcare delivery models is essential to improving patient outcomes, enhancing communication among healthcare providers, and optimizing the use of resources. These models emphasize collaboration among healthcare professionals, such as physicians, nurses, social workers, pharmacists, and therapists, to deliver comprehensive care. Communication in these teams is critical, impacting decision-making, care coordination, and patient satisfaction. This review critically analyzes interdisciplinary healthcare delivery models, the challenges related to communication, and the subsequent impact on patient outcomes. The findings suggest that effective communication and team-based care positively influence clinical outcomes, but challenges in coordination and healthcare systems remain barriers to success.